New Media and Learning in the 21st Century: A Socio-Cultural Perspective - LIN, Tzu-Bin (Springer, 2016)
This volume brings together conceptualizations and empirical studies that explore the socio-cultural dimension of new media and its implications on learning in the 21st century classroom. The authors articulate their vision of new-media-enhanced learning at a global level. The high-level concept is then re-examined for different degrees of contextualization and localization, for example how a specific form of new media (e-reader) changes specific activities in different cultures. In addition, studies based in Singapore classrooms provide insights as to how these concepts are being transformed and implemented by a co-constructive effort on the part of researchers, teachers and students. Singapore classrooms offer a unique environment to study the theory-practice nexus in that they are high achieving, implicitly grounded in the eastern cultural values and well-equipped with ICT infrastructure. While these studies are arguably the state-of-the-art exemplars that synergize socio-cultural and technological affordances of the current learning environments, they also serve as improvable ideas for further innovations. The interplay between theory and practice lends support to the reciprocal improvements for both. This book contributes to the continuing debate in the field, and will lead to better learning environments in the 21st century.